Two new species of Amorphophallus (Araceae: Thomsonieae) from Jawa, Indonesia - Yuzammi; Erlinawati, Ina; Hetterscheid, Wilbert (Phytotaxa, 2026)
Amorphophallus rosidii and A. raungensis are described as two new species found in the eastern part of East Jawa Province, Indonesia. Morphologically they resemble other Indonesian species like A. asper. On Jawa, the generally most similar species to both is A. annulifer but both have a much narrower appendix and no annulus at the base of the appendix. Amorphophallus rosidii is distinguished from A. raungensis by its much wider spathe base and heavy spotting (white) of the spathe inside and outside, and a much shorter style (only 1 mm vs. 4 mm in A. raungensis). An updated identification key to the species of Amorphophallus in Jawa is provided, accompanied by photographs for illustrative purposes.